Ecological Art Experience: How We Can Gain Experimental Control While Preserving Ecologically Valid Settings and Contexts - Carbon, Claus-Christian (Frontiers in Psychology, 2020)
One point that definitions of art experience disagree about is whether this kind of experience is qualitatively different from experiences related to ordinary objects and everyday contexts. Here, we follow an ecological approach assuming that art experience has its own specific quality that is, not least, determined by typical contexts of art presentation. Practically, we systematically observe typical phenomena of experiencing art in ecologically valid or real-world settings such as museum contexts. Based on evidences gained in this manner, we emulate and implement essential properties of ecological contexts (e.g., free choice of viewing distance and time, large scale of artworks and exhibition-like context) in controlled laboratory experiments. We found, for instance, that for large scale paintings by Pollock and Rothko preferred viewing distances as well as distances inducing most intense art experiences including Aesthetic Aha insights were much larger than typical viewing distances realized in lab studies. Following Carbon’s (2019) terminology of measurement strategies of art experience, the combined use of “Path #1” (real-world context) and “Path #2” (mildly controlled, still ecologically valid settings and contexts), enables us to understand and investigate much closer what is really happening when people experience art.